Linking Transformational Leadership, Compensation, and Employee Performance: The Mediationg Role of Work Engagement - Setyawati, Harini Abrilia; Wiwoho, Gunarso; Adi, Bagus Waskito; Hidayat, Aji; Hilabi, Oki Fad'ali (Journal of International Conference Proceedings, 2023)
This paper aims to examine the effect of transformational leadership and compensation on employee performance. The survey involved as many as 157 employees. The structural Equation Model is used to examine the research model. The statistical analysis tool used to test the hypothesis is Smart PLS. According to hypothesis testing analysis, this research concludes that transformational leadership significantly affects employee performance. However, contrary to the prediction, the result reported that compensation did not significantly impact employee performance. In addition, this study investigates work engagement as a mediating variable. The result showed that work engagement mediates the relationship of compensation with employee performance. Work engagement also significantly mediates the connection between transformational leadership and work performance. This study provides the managerial practice regarding improving employee performance through leadership, compensation and work engagement. Primarily, we recommend that SME leaders be more open and maintain employee development. Besides, compensation as a motivation strategy should be evaluated regarding the impact on employee work engagement.Keywords: transformational leadership, compensation, work engagement, and employee performance.